Examining Child Multitouch Screen Interaction Model: A Causal Effect Analysis - Liew, TzeHui; Lau, SiongHoe; Ismail, Hishamuddin (International Journal of Membrane Science and Technology, 2023)
Continual technological innovation, especially in educational technology for pre-school education, has led to a boom in new interaction characteristics in Child-Computer Interaction (CCI) research. The problem of limited screen sizes as a display and input device poses a design challenge that remains unanswered. Research with pre-school children requires careful attention to suitable methods, designs, and child-friendly models. The Child-Oriented TAM model has been adapted, and two new independent variables, namely screen size (SCS) and object size (OBS), were proposed for this study to gather feedback from children on their interaction satisfaction with multitouch screens. This study aims to validate the relationship between the variables of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), screen size (SCS), object size (OBS), and Satisfaction (SATIS) in pre-school children’s interaction with multitouch screens, and to test the moderating effects of age on this relationship. The findings of this study confirm that pre-school children’s satisfaction with multitouch screen interaction is determined by screen size and moderated by age. Pre-school educators, parents, and researchers can now have a better understanding of how screen size may affect children’s ability to interact with multitouch screens.